ANALISIS KOSA KATA PADA BUKU AJAR BAHASA ARAB TINGKATAN MI TERBITAN 2020 BERDASARKAN ACUAN CEFR (COMMON EUROPEAN FRAMEWORK OF REFERENCE): Vocabulary Analysis of 2020 Arabic Language Texbooks for Madrasah Ibtidaiyah Based on CEFR (Common European Framework of Reference) - Firmansyah, Haris; R.U., Nafisatul Izza; Mabruroh, Hani'atul; Mahliatussikah , Hanik (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2024)
The aim of this research is to determine the quality of the vocabulary contained in the Arabic language textbooks for Madrasah Ibtidaiyah level, published by the Ministry of Religious Affairs of the Republic of Indonesia in 2020, based on the CEFR (Common European Framework of Reference) guidelines. This study is purely a library research. The analytical technique used is content analysis, which is an effort to reveal the contents of a book. The results of this study indicate that the number of vocabulary words in the Arabic language textbooks for Madrasah Ibtidaiyah level published by the Ministry of Religious Affairs in 2020 does not meet the CEFR standard requirements. The vocabulary level in these books does not reach the A1 level (the lowest level) in the CEFR due to the fact that the textbooks contain 353 vocabulary words, whereas the A1 level of the CEFR requires 500 vocabulary words, thus needing an additional 147 words to reach the A1 level.